2009
DOI: 10.1037/a0016285
|View full text |Cite
|
Sign up to set email alerts
|

Social networks, personal values, and creativity: Evidence for curvilinear and interaction effects.

Abstract: Taking an interactional perspective on creativity, the authors examined the influence of social networks and conformity value on employees' creativity. They theorized and found a curvilinear relationship between number of weak ties and creativity such that employees exhibited greater creativity when their number of weak ties was at intermediate levels rather than at lower or higher levels. In addition, employees' conformity value moderated the curvilinear relationship between number of weak ties and creativity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
302
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(324 citation statements)
references
References 74 publications
16
302
1
5
Order By: Relevance
“…For example, Baer (2014) argued for the strength-of-weak ties perspective in creativity (see also Brass, 1995;Perry-Smith 2006;Perry-Smith & Shalley, 2003;Zhou, Shin, Brass, Choi & Zhang, 2009) and found that actors are more creative in idea networks of optimal size, weak strength, and high diversity, and when they score high on openness to experience. Similarly, Perry-Smith (2014) in an experimental study found tie strength to affect creativity through individual processing of non redundant knowledge.…”
Section: Ethical Leader Behaviorsmentioning
confidence: 99%
“…For example, Baer (2014) argued for the strength-of-weak ties perspective in creativity (see also Brass, 1995;Perry-Smith 2006;Perry-Smith & Shalley, 2003;Zhou, Shin, Brass, Choi & Zhang, 2009) and found that actors are more creative in idea networks of optimal size, weak strength, and high diversity, and when they score high on openness to experience. Similarly, Perry-Smith (2014) in an experimental study found tie strength to affect creativity through individual processing of non redundant knowledge.…”
Section: Ethical Leader Behaviorsmentioning
confidence: 99%
“…The interactional perspective on creativity suggests that the effective translation of ideas into action will depend on a variety of individual and situational attributes such as motivation, skills, personality, and contextual features (Zhou et al, 2009;Woodman et al, 1993). Individual cognitive biases may constrain creativity.…”
Section: Related Workmentioning
confidence: 99%
“…Segons Brass et al Intangible Capital -http://dx.doi.org/10.3926/ic.2011.v7n2.p585-610 -590 -(2004 influeixen en qüestions relatives al lideratge, el comportament i el rendiment en el treball. A mode d'exemple, diverses publicacions recents analitzen comportaments dels individus dins de l'organització amb la posició que aquests ocupen en la xarxa social per exemple pel que fa a lideratge (Goodwin et al, 2008), valors personals i creativitat (Zhou et al, 2009) i citizenship behavior (Bowler & Brass, 2006;Zagenczyk et al, 2008) entre d'altres.…”
Section: Les Xarxes Creen Un Context Tant D'oportunitats Com De Restrunclassified